A new species of Anheteromeyenia (Porifera, Demospongiae) with an emended diagnosis of the genus - Calheira, Ludimila; Pinheiro, Ulisses (Zootaxa, 2018)
Anheteromeyenia Schröder, 1927 (Spongillidae) was erected to comprise species of Heteromeyenia Potts, 1881 without microscleres. Until now, only four species of Anheteromeyenia are known, three from the Neotropical Region (A. cheguevarai, A. ornata and A. vitrea) and A. argyrosperma from the Nearctic Region. In the present study, we describe a new species of Anheteromeyenia from the Neotropical Region, which differs from other congeners in having only one category of megascleres, exclusively smooth oxeas. An identification key to species of Anheteromeyenia and an emended diagnosis of the genus are provided.